Impact of targeted PPARγ disruption on bone remodeling. (15th July 2015) - Cao, Jay; Ou, Guomin; Yang, Nianlan; Ding, Kehong; Kream, Barbara E.; Hamrick, Mark W.; Isales, Carlos M.; Shi, Xing-Ming
Highlights: A BMSC/progenitor cell specific PPARγ conditional knockout mouse model was generated using Col3.6-Cre line. The PPARγ cKO mice exhibited a moderate, site-dependent bone mass phenotype. The in vitro adipogenesis was abolished completely in bone marrow cells of PPARγ cKO mice. The differentiation and function of osteoclasts were not affected in the PPARγ cKO mice. Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ), known as the master regulator of adipogenesis, has been regarded as a promising target for new anti-osteoporosis therapy due to its role in regulating bone marrow mesenchymal stem/progenitor cell (BMSC) lineage commitment. However, the precise mechanism underlying PPARγ regulation of bone is not clear as a bone-specific PPARγ conditional knockout (cKO) study has not been conducted and evidence showed that deletion of PPARγ in other tissues also have profound effect on bone. In this study, we show that mice deficiency of PPARγ in cells expressing a 3.6 kb type I collagen promoter fragment (PPAR fl/fl :Col3.6-Cre) exhibits a moderate, site-dependent bone mass phenotype. In vitro studies showed that adipogenesis is abolished completely and osteoblastogenesis increased significantly in both primary bone marrow culture and the BMSCs isolated from PPARγ cKO mice. Histology and histomorphometry studies revealed significant increases in the numbers of osteoblasts and surface in the PPARγ cKO mice. Finally, we found that neither the differentiation nor the function of osteoclasts was affected in the PPARγ cKO mice. Together, our studies indicate that PPARγ plays an important role in bone remodeling by increasing the abundance of osteoblasts for repair, but not during skeletal development.